La méthode des analogues : reproduire le caractère saisonnier de la distribution d’eau potable dans les stations touristiques de montagne - Martin Calianno (Revue de Géographie Alpine)
Few of the integrated water management surveys or water offer-demand models include a description of the seasonality of demand with sufficiently fine time steps (monthly and lower). The analogues method was developed with as a case study the tourist resort of Megève (Haute-Savoie, France), presenting a strong seasonal variability in the demand for drinking water. The method is intended for decision-makers and urban planners, because it makes it possible to predict the seasonality of drinking water distribution in Alpine regions where data on water use is rarely available. It involves monitoring on a sample of domestic drinking-water meters with a daily resolution, to identify the different demand regimes and use them as « patterns » to reproduce the municipal distribution signal. Analysis of the distribution of drinking water has highlighted two types of variability : high frequency (weekly) and low frequency (seasonal). The monitoring underlined the influence of the type of building and the permanence of the habitat on the drinking water distribution regimes. Finally, the analogues method is considered to be effective in reproducing the low and high frequency variability of the distribution. The size and representativeness of the user sample are the most important factors to be taken into account in its implementation.